Spinal muscular atrophy with progressive myoclonic epilepsy - rare case report from India - Nagpal, Tuhina; Agrawal, Kamlesh; Gupta, Ashok; Mathur, Priyanshu (International Journal of Contemporary Pediatrics, 2021)
Spinal muscular atrophy with progressive myoclonic epilepsy is a rare genetic disorder characterized by progressive muscular weakness and myoclonic seizures. Herein we report an Indian boy with myoclonic seizures followed by progressive weakness of both lower limbs and detected with heterozygous mutation in N-acylsphingosine amidohydrolase 1 (ASAH1) gene causing spinal muscular atrophy with progressive myoclonic epilepsy.